Lessons learned in the development of a nurse‐led family centered approach to developing a holistic comprehensive clinic and integrative holistic care plan for children with cerebral palsy. Issue 1 (9th August 2021) - Love, Lamara; Newmeyer, Amy; Ryan‐Wenger, Nancy; Noritz, Garey; Skeens, Micah A.
Abstract: Clinical Problem: Children with cerebral palsy (CP) typically receive care from multiple specialty providers including Developmental Pediatrics, Orthopedics, Physical Medicine, Occupational Therapy, Physical Therapy, Speech Therapy, Clinical Social Work, Clinical Nutrition, Nursing and Orthotists, which often require many individual visits to the hospital annually. The potential for conflicting plans of care is increased by this fragmented approach, which may lead to duplication of services and increased healthcare costs. Solution: To address the problem and alleviate burden for families, the Comprehensive Cerebral Palsy Program implemented a nurse‐led comprehensive interdisciplinary team approach to provide optimal care coordination to patients and families, using an Integrative Holistic Care Plan (IHCP). During an annual 3–4 hour Comprehensive CP Clinic appointment, a team of specialists meets with the family, and a holistic, evidence‐based plan of care is developed. The family‐centered care plan includes summaries of each discipline's plan of care with individualized goals, recommendations, and evidence‐based outcomes. After the visit, the plan of care is communicated with the family, primary care provider, and other community providers to ensure continuity of care. Results: Early in the program and electronic IHCP development stage, clinical, and financial outcomes were improved. In addition to significant cost savings, family satisfaction surveys showed continuous improvement in the areas of access, communication, and coordination of care. Practice Implications: Nurses working in interdisciplinary clinics are in a position to facilitate improved outcomes by developing and implementing a family‐centered care plan that provides a comprehensive holistic approach to impacting the areas of quality, effectiveness, and efficiency of care delivery. The use of an IHCP decreases fragmentation of care and duplication of services leading to healthcare cost savings and enhanced patient satisfaction.